CLASSIFICATION OF RISKS OF BANK RETAIL AND FACTORS AFFECTING IT - Козьмук , Наталія; Демченко , Андрій (Socio-economic relations in the digital society, 2019)
The concept of risk, economic risk, bank risk, and the risk of banking retail is considered in this paper. Conditions of economic risk are described. In addition, groups of risks are described which depend on the direction of implementation policy implementation. The factors on which the level of banking retail banking risk depends on are considered. The division of risks according to the stages of innovative measures implemented by the banking institution is implemented. The list of goals to be achieved during the implementation of measures on innovative retail banking is proposed.